h - Schomburg, Dietmar; Schomburg, Ida.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Springer Handbook of Enzymes provides data on enzymes sufficiently well characterized. It offers concise and complete descriptions of some 5,000 enzymes and their application areas. Data sheets are arranged in their EC-Number sequence and the volumes themselves are arranged according to enzyme classes. This new, second edition reflects considerable progress in enzymology: many enzymes are newly classified or reclassified. Each entry is correlated with references and one or more source organisms. New datafields are created: application and engineering (for the properties of enzymes where the sequence has been changed). The total amount of material contained in the Handbook has more than doubled so that the complete second edition consists of 39 volumes as well as a Synonym Index. In addition, starting in 2009, all newly classified enzymes are treated in Supplement Volumes. Springer Handbook of Enzymes is an ideal source of information for researchers in biochemistry, biotechnology, organic and analytical chemistry, and food sciences, as well as for medicinal applications.
3.4.11.24 aminopeptidase S -- 3.4.17.23 angiotensin-converting enzyme 2 -- 3.4.22.69 SARS coronavirus main proteinase -- 3.4.22.70 sortase A -- 3.4.22.71 sortase B -- 3.4.23.50 human endogenous retrovirus K Endopeptidase -- 3.4.23.51 HycI peptidase -- 3.4.24.87 ADAMTS13 endopeptidase -- 3.4.25.2 HslU-HslV peptidase -- 3.5.1.99 fatty acid amide hydrolase -- 3.5.1.100 (R)-amidase -- 3.5.1.101 L-proline amide hydrolase -- 3.5.1.102 2-amino-5-formylamino-6-ribosylaminopyrimidin-4(3H)-one 5$1 (B- monophosphate deformylase -- 3.5.1.103 N-acetyl-1-D-myo-inositol-2-amino-2-deoxy-a- D-glucopyranoside deacetylase -- 3.5.1.104 peptidoglycan-N-acetylglucosamine Deacetylase -- 3.5.1.105 chitin disaccharide deacetylase -- 3.5.1.106 N-formylmaleamate deformylase -- 3.5.1.107 maleamate amidohydrolase -- 3.5.1.108 UDP-3-O-acyl-N-acetylglucosamine Deacetylase -- 3.5.2.19 streptothricin hydrolase -- 3.5.99.8 5-nitroanthranilic acid aminohydrolase -- 3.6.1.53 Mn2+-dependent ADP-ribose/CDP-alcohol Diphosphatase -- 3.6.1.54 UDP-2,3-diacylglucosamine diphosphatase -- 3.6.4.12 DNA helicase -- 3.6.4.13 RNA helicase -- 3.7.1.11 cyclohexane-1,2-dione hydrolase -- 3.7.1.12 cobalt-precorrin 5A hydrolase -- 3.7.1.13 -hydroxy-6-oxo-6-(2-aminophenyl)hexa-2,4- dienoate hydrolase -- 4.1.1.87 malonyl-S-ACP decarboxylase -- 4.1.1.88 biotin-independent malonate decarboxylase -- 4.1.1.89 biotin-dependent malonate decarboxylase -- 4.1.1.90 peptidyl-glutamate 4-carboxylase -- 4.1.2.43 3-hexulose-6-phosphate synthase -- 4.1.2.44 benzoyl-CoA-dihydrodiol lyase -- 4.1.2.45 trans-o-hydroxybenzylidenepyruvate hydratase-aldolase -- 4.1.2.46 aliphatic (R)-hydroxynitrile lyase -- 4.1.3.41 3-hydroxy-D-aspartate aldolase -- 4.1.99.13 (6-4)DNA photolyase -- 4.1.99.14 spore photoproduct lyase -- 4.1.99.15 S-specific spore photoproduct lyase -- 4.2.1.114 methanogen homoaconitase -- 4.2.1.115 UDP-N-acetylglucosamine 4,6-dehydratase (inverting) -- 4.2.1.116 3-hydroxypropionyl-CoA dehydratase -- 4.2.1.117 2-methylcitrate dehydratase (2-methyl-transaconitate forming) -- 4.2.1.118 3-dehydroshikimate dehydratase -- 4.2.1.119 enoyl-CoA hydratase 2 -- 4.2.1.120 4-hydroxybutanoyl-CoA dehydratase -- 4.2.1.121 colneleate synthase -- 4.2.3.28 ent-cassa-12,15-diene synthase -- 4.2.3.29 ent-sandaracopimaradiene synthase -- 4.2.3.30 ent-pimara-8(14),15-diene synthase -- 4.2.3.31 ent-pimara-9(11),15-diene synthase -- 4.2.3.32 levopimaradiene synthase -- 4.2.3.33 stemar-13-ene synthase -- 4.2.3.34 stemod-13(17)-ene synthase -- 4.2.3.35 syn-pimara-7,15-diene synthase -- 4.2.3.36 terpentetriene synthase -- 4.2.3.37 epi-isozizaene synthase -- 4.2.3.38 a-bisabolene synthase -- 4.2.3.39 epi-cedrol synthase -- 4.2.3.40 (Z)-g-bisabolene synthase -- 4.2.3.41 elisabethatriene synthase -- 4.2.3.42 aphidicolan-16b-ol synthase -- 4.2.3.43 fusicocca-2,10(14)-diene synthase -- 4.2.3.44 isopimara-7,15-diene synthase -- 4.2.3.45 phyllocladan-16a-ol synthase -- 4.2.3.46 a-farnesene synthase -- 4.2.3.47 b-farnesene synthase -- 4.2.3.48 (3S,6E)-nerolidol synthase -- 4.2.3.49 (3R,6E)-nerolidol synthase -- 4.2.99.20 2-succinyl-6-hydroxy-2,4-cyclohexadiene-1-carboxylate synthase -- 4.2.99.21 isochorismate lyase -- 4.3.1.26 chromopyrrolate synthase -- 4.3.1.27 threo-3-hydroxy-D-aspartate ammonia-lyase -- 4.3.99.2 carboxybiotin decarboxylase -- 4.99.1.8 heme ligase -- 5.1.99.5 hydantoin racemase -- 5.3.1.27 6-phospho-3-hexuloisomerase -- 5.3.1.28 D-sedoheptulose 7-phosphate isomerase -- 5.5.1.14 syn-copalyl-diphosphate synthase -- 5.5.1.15 terpentedienyl-diphosphate synthase -- 5.5.1.16 halimadienyl-diphosphate synthase -- 5.99.1.4 2-hydroxychromene-2-carboxylate isomerase -- 6.1.1.27 O-phospho-L-serine-tRNA ligase -- 6.2.1.35 ACP-SH:acetate ligase -- 6.2.1.36 3-hydroxypropionyl-CoA synthase -- 6.3.1.13 L-cysteine:1D-myo-inositol 2-amino-2-deoxy-a-D-glucopyranoside ligase -- 6.3.1.14 diphthine-ammonia ligase -- 6.3.2.31 coenzyme F420-0:L-glutamate ligase -- 6.3.2.32 coenzyme g-F420-2:a-L-glutamate ligase -- 6.3.2.33 coenzyme g-F420-2:a-L-glutamate ligase -- 6.3.2.33 tetrahydrosarcinapterin synthase -- 6.3.2.34 coenzyme F420-1:g-L-glutamate ligase -- 6.3.2.35 D-alanine-D-serine ligase -- 6.3.2.36 4-phosphopantoate-b-alanine ligase.s
Keywords: Life sciences; Medicine; Toxicology; Biotechnology; Food science; Veterinary medicine; Biochemistry; Life Sciences; Biochemistry, general; Molecular Medicine; Pharmacology/Toxicology.; Food Science; Biotechnology; Veterinary Medicine